Efficacy and safety of video double-lumen tube intubation in lateral position in patients undergoing thoracic surgery: a randomized controlled trial - Qianqian Rao; Hong Yu; Ping Li; Gongwei Zhang; Jun Zeng; Qiang Pu; Hai Yu (BMC Anesthesiology, 2024)
Abstract Background Video double-lumen tube (VDLT) intubation in lateral position is a potential alternative to intubation in supine position in patients undergoing thoracic surgery. This non-inferiority trial assessed the efficacy and safety of VDLT intubation in lateral position. Methods Patients (18–70 yr) undergoing right thoracoscopic lung surgery were randomized to either the left lateral position group (group L) or the supine position group (group S). The VDLT was placed under video larygoscopy. The primary endpoint was the intubation time. Secondary endpoints included VDLT displacement rate, intubation failure rate, the satisfaction of surgeon and nurse, and intubation-related adverse events. Results The analysis covered 80 patients. The total intubation time was 52.0 [20.4]s in group L and 34.3 [13.2]s in group S, with a mean difference of 17.6 s [95% confidence interval (CI): 9.9 s to 25.3 s; P = 0.050], failing to demonstrate non-inferiority with a non-inferiority margin of 10 s. Group L, compared with group S, had significantly lower VDLT displacement rate (P = 0.017) and higher nurse satisfaction (P = 0.026). No intubation failure occurred in any group. Intubation complications (P = 0.802) and surgeon satisfaction (P = 0.415) were comparable between two groups. Conclusions The lateral VDLT intubation took longer time than in the supine position, and non-inferiority was not achieved. The incidence of displacement as the secondary endpoint was lower in the L group, possibly due to changing body positions beforehand. The indication of lateral VDLT intubation should be based on a balance between the safety of airway management and the lower incidence of displacement. Trial registration The study was registered at Chictr.org.cn with the number ChiCTR2200064831 on 19/10/2022.